Pre-Service Teachers' Approaches to English Language Instruction: Insights from EFL Pre-Service Teachers - Nurul Aqilah; Titin Rahmiatin Rahim; Andi Rachmawati Syarif (Institut Agama Islam Negeri Palopo, 2024)
This study delves into the efficacy of microteaching as a pedagogical tool for enhancing reflective practices among pre-service teachers. Employing a case study approach, the research investigates the experiences and reflections of a cohort of pre-service teachers who participated in microteaching practice over a specified period. The study aims to discern the direct influence of microteaching on the development of reflective practices and explore the underlying mechanisms through which this impact occurs. This research elucidates the nuanced relationship between microteaching and reflective practices through qualitative data analysis gathered from participant reflections and interviews. Pre-service teachers' written reflections and open-ended interviews are used to collect data on their reflective teaching. The reflective journal records students' experiences during microteaching practice, while interviews provide insights into their reflective practices and their approaches to their professional growth. The findings of this study show that reflecting on teaching practices can influence the improvement of pre-service teachers' instructional strategies. This research highlights the importance of instructional strategies in implementing learning innovations. Indicators of instructional strategies were found: teaching plans and approaches, goals and objectives, teaching experiences, methods and strategies, memorable classroom events, and barriers and solutions.